Beyond conventional healthcare for mental health problems: Experiences of existential group conversations - Inger Jansson; Karin Thörne; Daniel Masterson (Scandinavian Journal of Occupational Therapy)
Background Mental health problems (MHP) are a major public health challenge. Conventional healthcare has shown limitation on reducing MHP and there is a call for offering methods beyond healthcare as well as improve access to healthcare.Aims To explore experiences among people having MHP of (i) taking part in existential conversations in groups beyond conventional healthcare and (ii) seeking and receiving conventional healthcare.Materials and methods Four focus group interviews were conducted after finishing existential conversations in groups. Data was analyzed following thematic analysis.Results The theme Access to a community for exploration and acceptance describes communication through impressions and expressions together with others. A reflective perspective on everyday life, describes re-evaluation through reflection. Within the theme Experiences of healthcare related encounters, referring to the second aim, participants recollected feelings of disconnectedness, difficulties verbalizing MHP and dealing with rigid, standardized measures.Conclusion Existential conversations in group may contribute to a more reflected doing in accordance with one’s own values as well as improved mental health literacy. Design and measures within healthcare need to explicitly address MHP and consider individual’s own preferences.Significance This study contributes to understanding of coping with MHP in everyday life from an existential perspective.